EMPOWERMENT OF SANTRIPRENEUR THROUGH E-COMMERCE STARTUP (Study of Modern Islamic Boarding School Datok Sulaiman, Palopo City) - M Wahyuddin Abdullah; Abdul Wahid Haddade; Ahmad Nouruzzaman (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2020)
This research aims to develop empowerment with role model empowerment of santri through e-commerce startups embodying futuristic santripreneur in Pesantren Modern Datok Sulaiman Palopo. This field research study is classified in qualitative descriptive using phenomenological and participatory action research to produce information, knowledge, skills solve problems on research subjects, and apply actions in natural settings. The results of this study, the empowering process of santri was conducted together with teachers and board of santri PMDS Palopo through a new media called "Ala Santri" tagged "Santri Pengusaha." This empowerment process principally develop santri potential and create the santri independent through e-commerce startups.  This empowerment is implemented in five stages: the stage of human resource development, the stage of empowerment development through e-commerce startups, the evaluation or diagnosis stage of the problem, the stage of transformation of will in empowering, and the generalization and stabilization of changes in empowerment. There are two role models of empowering santri through e-commerce startups, namely business to consumer business model built independently by creating new media in the form of websites by maximizing transactions through chat, and Non-Business Electronic Commerce model that focuses on building the image PMDS Palopo.